2019
DOI: 10.1002/jso.25736
|View full text |Cite
|
Sign up to set email alerts
|

Potential survival benefit of radiofrequency ablation for small solitary intrahepatic cholangiocarcinoma in nonsurgically managed patients: A population‐based analysis

Abstract: Background Little data regarding the selection of nonsurgical therapies for localized intrahepatic cholangiocarcinoma (ICC) are available. Methods A cohort of nonsurgically managed patients with American Joint Commission on Cancer clinical stage I/II ICC in the United States from 2004 to 2013 were identified in the National Cancer Database. Overall survival (OS) was compared according to treatment options (radiofrequency ablation [RFA] vs chemoradiotherapy) using propensity‐score matching. Results Among 505 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Several researches have shown that these treatments, alone or in combination with chemotherapy, improve Overall Survival (OS) [ 24 ]. In a cohort of non surgical treated small (≤ 5 cm) iCCA, staged as AJCC I/II, RFA-treated patients showed better survival respect to chemoradiotherapy [ 23 ], results reported by a recent meta-analysis, too [ 24 ]. Consequently, RFA is the treatment of choice in small ICCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have shown that these treatments, alone or in combination with chemotherapy, improve Overall Survival (OS) [ 24 ]. In a cohort of non surgical treated small (≤ 5 cm) iCCA, staged as AJCC I/II, RFA-treated patients showed better survival respect to chemoradiotherapy [ 23 ], results reported by a recent meta-analysis, too [ 24 ]. Consequently, RFA is the treatment of choice in small ICCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different locoregional treatments, RFA as compared with palliative treatment has been widely suggested to carry a survival benefit in small, solitary iCCA or in patients with local recurrence or residual tumor after surgery with curative intent. For example, in a cohort of nonsurgically-managed patients with small ( ≤ 5 cm) solitary iCCA without vascular invasion who were staged as AJCC I/II in the National Cancer Database, RFA-treated patients showed better survival compared with chemoradiotherapy [152] , a finding that has been supported by a recent meta-analysis [153] . Therefore, in the subset of unresectable patients with small iCCA, RFA is emerging as a treatment of choice similar to small, early hepatocellular carcinoma, although this needs to be supported by adequate trials.…”
Section: Locoregional Liver-directed Therapiesmentioning
confidence: 88%
“…While the median survival rate of resection ICC patients was 27.6 months, it was only 12.9 months for the non-surgical candidates with varied palliative treatment in a study by Dhanasekaran et al ( 21 ). Recently, Wu et al ( 22 ) found that for patients with unresectable ICC, RFA was associated with significantly better survival rates compared with chemoradiotherapy. RFA was recommended as one of the standard treatments for ICC in the European Association for the Study of the Liver (EASL) guidelines, although the evidence level was only C2 ( 6 ).…”
Section: Discussionmentioning
confidence: 99%